Religious Functions Brick Structure P.6 Kedaton Temple - Retno Purwanti (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2021)
Abstract: Kedaton temple is one of the temple complex in Muarajambi Temple site and has 14 pages. Each page is separated by a wall around the brick. On some pages there is a brick structure, one of which is coded P.6. This structure berdenah rectangular and equipped with space. Archaeological finds at this location indicate religious function. The purpose of this research is to know the religious function of structure P.6 based on archaeological evidence. Data collected through excavation and literature review. Data analysis is done by identification of archaeological remains, then associated with the form and function. The result of this research is celupak, broken bowl and crock which depict, that Structure P.6 is dharmmasala, place to do Buddhist pujabhakti. Keywords: Kedaton Temple; structure; function; dharmmasala.